Wartościowanie zdrowia w opinii pielęgniarek w odniesieniu do zmiennych społeczno - demograficznych = Health evaluation with relation to socio-demographic variables - nurses' opinions - Alina Deluga; Beata Dobrowolska; Bogumiła Kosicka; Agnieszka Brzozowska (Kazimierz Wielki University, 2016)
Deluga Alina, Dobrowolska Beata, Kosicka Bogumiła, Brzozowska Agnieszka. Wartościowanie zdrowia w opinii pielęgniarek w odniesieniu do zmiennych społeczno - demograficznych = Health evaluation with relation to socio-demographic variables - nurses' opinions. Journal of Education, Health and Sport. 2016;6(4):167-180. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50028 http://ojs.ukw.edu.pl/index.php/johs/article/view/3460   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016.     Wartościowanie zdrowia w opinii pielęgniarek w odniesieniu do zmiennych społeczno - demograficznych   Health evaluation with relation to socio-demographic variables - nurses' opinions   Alina Deluga, Beata Dobrowolska, Bogumiła Kosicka, Agnieszka Brzozowska   1. dr n med. Alina Deluga Alina Deluga, MSc, PhD Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, UM Lublin Department of Family Medicine and Community Nursing, Medical University of Lublin   2. dr n hum. Beata Dobrowolska Beata Dobrowolska, MSc, PhD Katedra Rozwoju Pielęgniarstwa, UM Lublin Department of Nursing Development, Medical University of Lublin   3. dr n med. Bogumiła Kosicka Bogumila Kosicka, MSc, PhD Katedra i Zakład Zarządzania w Pielęgniarstwie, UM Lublin Department of Management in Nursing, Medical University of Lublin   4. mgr Agnieszka Brzozowska Agnieszka Brzozowska, MSc Zakład Matematyki i Biostatystyki Medycznej, UM Lublin Department of Mathematics and Medical Biostatistics, Medical University of Lublin     Słowa kluczowe: wartościowanie zdrowia, pielęgniarki, zmienne społeczno-demograficzne Key words: health evaluation, nurses, socio-demographic variables     Streszczenie Wstęp Zdrowie stanowi jedną z najważniejszych wartości, na podstawie której dokonuje się wyboru zachowań zdrowotnych będących składową stylu życia człowieka. Cel pracy Celem pracy jest ocena wartości zdrowia w opinii pielęgniarek w zależności od zmiennych społeczno - demograficznych. Materiał i metody Badania przeprowadzono w 2014 i 2015 roku. Objęto nimi 191 pielęgniarek, będących studentami - studiów pomostowych licencjackich i magisterskich w wieku od 22 do 47 lat. Do zebrania materiału użyto standaryzowanego narzędzia badawczego - LKZ (Lista Kryteriów Zdrowia), autorstwa Z. Juczyńskiego. Wyniki Przeprowadzone badania wykazały, że pielęgniarki najwyższą wagę przypisują zdrowiu rozumianemu w kategorii właściwość i stan, określanemu przez stwierdzenia "nie odczuwać żadnych dolegliwości fizycznych", "mieć sprawne wszystkie części ciała" oraz "czuć się szczęśliwym przez większość czasu". Ankietowani po 40 roku życia, będący w związku małżeńskim, zamieszkujący małe miasta istotnie częściej wybierali kryterium zdrowia "nie odczuwać żadnych dolegliwości fizycznych", (p=0,03) w porównaniu z badanymi z młodszych grup wiekowych, którzy częściej wskazywali na kryterium "potrafić dobrze współżyć z innymi ludźmi" (p=0,01). Wnioski Ocena znaczenia i wartościowania zdrowia jest ważnym elementem oceny świadomości prozdrowotnej pielęgniarek i jest zależna od zmiennych społeczno-demograficznych. Pielęgniarki najwyższą wagę przypisują zdrowiu utożsamianemu z właściwością i stanem, co charakteryzuje instrumentalne podejście do zdrowia.         Abstract Introduction Health constitutes one of the most important values in human life and the basis for people's decisions on their health behaviours which are components of their lifestyle. Aim The main aim of this paper is to evaluate the value of health in the opinion of nurses with relation to socio-demographic variables. Material and methods The study was carried out in years 2014 and 2015. It included 191 nurses who were students of nursing, both of bachelor bridging and master studies, from 22 to 47 years of age. The data were collected with a standardized research tool - the List of Health Criteria (LKZ Lista Kryteriów Zdrowia) by Z. Juczyński. Outcomes The study outcome showed that the respondents pay much attention mainly to health understood in the categories of property and state, described by the following statements: "not experiencing any ailments", "having all the body parts healthy" and "feeling happy most of the time". Those surveyed at the age of 40 plus, married and living in small towns more often chose the health criterion "not experiencing any ailments" (p = 0.03) than those younger ones who primarily marked the category "being able to efficiently coexist with other people" (p=0.01). Conclusions Health evaluation and significance are prominent elements of pro-health awareness in the nurses. Moreover, they/health behaviours depend on socio-demographic variables. The nurses pay much attention to health being associated with property and state, which characterizes an instrumental approach to health.